Plan de intervención psicopedagógica para el mejoramiento de la autoeficacia académica en estudiantes de la modalidad intensiva del bachillerato general unificado, en la unidad educativa Pueblo Nuevo. - Campuzano Plaza, Nahomy Juleimy (2025)
The research was conducted at the Unidad Educativa “Pueblo Nuevo” and aimed to design a psychopedagogical intervention plan to strengthen academic self-efficacy in students of the intensive modality of the General Unified Baccalaureate. It started from the observation that, in accelerated educational contexts with limited resources, students faced difficulties in consolidating a solid academic self-efficacy profile, which was reflected in fragile autonomy, self-regulation, and intrinsic motivation. The general objective focused on developing a proposal based on the theories of Bandura and Zimmerman, integrating self-efficacy with contemporary models of psychopedagogical intervention. The methodology followed a mixed approach with a pragmatic paradigm, using a non-experimental and descriptive-propositive design; quantitative and qualitative data collection techniques were applied, including the Academic Self-Efficacy Scale, observation guide, and checklist. The results revealed a medium-high level of general self-efficacy (M=105), but significant discrepancies were identified between declared confidence and observed behaviors, particularly in areas such as emotional regulation, resilience, academic initiative, intrinsic motivation, and problem-solving. Based on this diagnosis, a structured plan of nine sessions was designed, integrating active and contextualized strategies to address the detected deficiencies, prioritizing the progressive development of self-regulatory competencies. Validation by professional judgment confirmed the relevance, feasibility, and effectiveness of the proposal, with positive consensus on criteria of relevance, sustainability, coherence, and methodological rigor. In conclusion, the study provided a theoretical and practical basis for understanding and strengthening academic self-efficacy in the intensive modality, consolidating a replicable psychopedagogical intervention model for similar educational contexts.